PSYCHOLOGICAL MECHANISMS LINKING SOCIAL MEDIA USE AND ADOLESCENT MENTAL HEALTH: A NARRATIVE REVIEW - Cieślak, Natalia; Chodkowska, Agata; Cyrkler, Aleksandra; Czyżak, Kamila; Marzec, Urszula; Dąbek, Karol; Rajca, Eliza; Giza, Agnieszka; Giza, Paulina; Wymoczył, Karolina (International Journal of Innovative Technologies in Social Science, 2026)
The rapid expansion of social media use among adolescents has coincided with increasing concerns about their mental health. Rates of depressive symptoms and anxiety have risen in many countries, leading researchers to question whether intense online engagement may contribute to these trends. This article presents a narrative review of recent literature to examine current evidence on the relationship between social media use and mental health outcomes in adolescents and young adults, with particular attention to problematic use, emotional investment, gender differences, Fear of Missing Out (FOMO), and sleep disturbances.This study is based on a narrative review of recent systematic reviews, meta-analyses, and longitudinal research. Research findings indicate that the association between social media use and mental health is small but relatively consistent across studies. Importantly, overall screen time appears to be a weak predictor of psychological distress. Patterns of engagement—especially passive use, compulsive checking, and high emotional investment—show stronger associations with depressive and anxiety symptoms. Sleep disturbances emerge as an important mediating factor that may partially explain this link.The evidence indicates that social media is not inherently harmful. However, it may intensify existing vulnerabilities, particularly among adolescent girls. Preventive efforts should therefore focus on digital literacy, emotional regulation, and sleep hygiene rather than simple time restrictions.